ANALISIS PEMBELAJARAN MATEMATIKA PADA SEKOLAH YANG MENERAPKAN PENDEKATAN PMRI DAN SEKOLAH YANG TIDAK MENERAPKAN PENDEKATAN PMRI DI KOTA YOGYAKARTA - Negara, Hasan S; Sujadi, Imam; Pangadi, Pangadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this study were describing the process of mathematics learning and its problem solving for primary III students whom school was applying PMRI approach and non applying PMRI approach. This research was a qualitative case study type. The subject of this study divided into 2, which were: subject for searching information about learning process and subject for searching information about problem solving. Subject in this study were 2 primary teachers, 1 teacher from SD Kanisius Demangan Baru and 1 teacher from SD Muhammadiyah Demangan, another subject were 4 students, 2 students from SD Kanisius Demangan Baru and 2 students from SD Muhammadiyah Demangan. The data was divided into 2, which were learning process data that contain about teacher and student activities in learning and mathematical problem solving data that contain about information problem solving in mathematics. Learning process data was collected from recording transcription result of learning activities toward two observations, while mathematical problem solving data was collected by using the think aloud method. The result revealed that mathematical problem solving abilities in students with high ability type in school PMRI approach better than students in schools that do not implement PMRI approach, but problem solving abilities in students with low ability types in school PMRI approach is not better than students in schools that do not applying the PMRI approach.Key words: Learning process, problem solving, PMRI approac